MENINGKATKAN PENGHASILAN UMKM KERUPUK UDANG DI DESA JENEBORA DENGAN TEKNOLOGI PEMASARAN MODERN - Misrianto, Misrianto; Patrecia Simarmata, Roulina (JURNAL PENGABDIAN PAPUA, 2024)
ocialization to MSMEs in Jenebora Village highlights the importance of marketing strategies through social media to maximize local potential such as shrimp-based products. Social media as a digital marketing tool helps expand markets, increase competitiveness, and support sustainable economic growth through innovation and effective marketing. Micro, small and medium enterprises (MSMEs) often face obstacles regarding poor marketing. Jenebora Village has abundant shrimp resources, so the MSMEs here almost sell food products based on shrimp ingredients, such as shrimp paste, shrimp pentol, shrimp crackers. This service aims to increase the income of MSMEs in Jenebora Village by providing an understanding of the importance of marketing modrend and following the times. The object of service was carried out an interview survey method with certain indicators carried out before the assistance. The results of PkM show that there is a change in the knowledge of PkM Objects regarding product marketing, changes occur quite significantly to the object of PkM, PkM Objects Shrimp crackers understand knowledge about the importance of marketing in a modern way from 50 to 100%, while the increase in business progress through modern product marketing from 40 to 75%, ordering PkM object products online from 40 to 80%. Keywords: Direction; Marketing; Earning; UMKM; Business